We can think of this dilation as this: if the center of dilation is P and the factor of dilation is k = 1/2, we can draw the image triangle as:
This way, the segments P'R' and P'Q' have half the length of PR and PQ respectively.
The segment RQ passes through the origin of coordinates. As no other image segment intersects with RQ, we know that no image segment passes through the origin of coordinates.
Answer:
No segments of triangle P'Q'R' pass trhough the origin.
solve for x
Answer:
a system of equations , as below
Step-by-step explanation:
4y-x
2x-4
x+y
use any two of the above to find a formula for one of the variables since they are all equal to each other.. btw.. it makes it much easier .. that they are all equal. :)
2x-4=x+y ⇒ x-4=y use this to plug into the y in the top formula
4(x-4)-x=2x-4 ⇒ 4x-16-x=2x-4 ⇒ 3x-16=2x-4 ⇒ x=12 yay! ;) now plug in 12 for x
2(12)-4=(12)+y ⇒ 24-4 = 12 +y ⇒ 8=y yay ! now we have both x and y
x=12
y= 8
this checks by plugging in the two number found for x & y (btw I had to try this about 4 times ) :P I kept messing up the algebra which is soooo easy to mess up.
Let's solve the equation:
9x + 27 = 9 ( x + 2 ) + 9 ← Distribute 9 to the x and 2
9x + 27 = 9x + 18 + 9 ← Combine like terms
9x + 27 = 9x + 27 ← Subtract 27 from both sides
9x = 9x
0 = 0
{Infinitely many solutions would be correct because no matter what x is, it will always equal each other the both sides of the equation because it is 9 times x on both sides.}
hope this helps..........
Answer:
x=1
Step-by-step explanation:
9x+27=9(x+2)+9
9x+27=9x+18+9
9x+27=9x+27
9x=9x
x=1
Answer:
integers from -1 ≤x≤2
Step-by-step explanation:
The domain is the value of the input or the x values
The domain is -1,0,1,2
integers from -1 ≤x≤2
The simplification of the expression 3(2x + y is 6x +3y
According to the distributive property, multiplying the sum of two or more addends by a number will give the same result as multiplying each addend individually by the number and then adding the products together.
For example, a ( x +y) can be written in the form
ax + ay .
Similarly, simplifying 3(2x +y) using distributiveproperty means
3× 2x + 3 × y
= 6x + 3y
Therefore the simplification of the expression 3(2x + y) is 6x + 3y.
learn more about distributive property from
#SPJ3
Answer:
the solution is just 6x+3y
thats all
Answer:
$23.64
Step-by-step explanation:
12 * $1.97 = $23.64